2018
DOI: 10.1039/c8nr03830a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wave pumped single-mode nanolasers in inorganic perovskites with robust stability and high quantum yield

Abstract: Perovskite lasers have aroused great interest in recent years due to their ultra-low lasing threshold, high quantum yields, easily tuned emission colors and great potential for electrically pumped nanolasing, which opens up new possibilities in obtaining highly coherent light sources at the nanoscale. Compared with the widely studied organic-inorganic hybrid perovskites, the inorganic (CsPbX3) have gradually become an emerging research focus because of their relatively better stability. However, some problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…They uncovered that both cw and pulsed lasing originate from polariton modes near the bottleneck region on the lower polariton branch, with a vacuum Rabi splitting of 0.20 ± 0.03 eV. These results give the NWs promising potentials toward cw pumped lasing application …”
Section: Different Dimensional Metal Halide Perovskites For Lasingmentioning
confidence: 91%
See 1 more Smart Citation
“…They uncovered that both cw and pulsed lasing originate from polariton modes near the bottleneck region on the lower polariton branch, with a vacuum Rabi splitting of 0.20 ± 0.03 eV. These results give the NWs promising potentials toward cw pumped lasing application …”
Section: Different Dimensional Metal Halide Perovskites For Lasingmentioning
confidence: 91%
“…Jiang et al received single‐mode cw lasing with high stability from inorganic CsPbBr 3 perovskite NWs during 4 K running temperature. It was found that the NW can exhibit a narrow lasing linewidth of ≈0.09 nm at a threshold of 1.45 nW . Zhu and co‐workers conducted cw‐pumped PL measurement with single‐crystal CsPbBr 3 perovskite NWs that grown from solution.…”
Section: Continuous‐wave Pumped Perovskite Lasingmentioning
confidence: 99%
“…However, most research has been focused on encapsulating PQDs with polymers, which is unfavorable for higher‐temperature environment applications . Second, the ability to obtain a stable, single layer of PQDs microspheres which can be used to achieve secondary nanostructures on micron block materials is highly desired . Third, the current most popular hydrolysis encapsulation method requires toluene as a solvent, along with relatively high humidity, which is fatal to iodine‐based perovskites .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, single‐crystalline micro‐/nanostructures with low defect densities are expected as an ideal platform for achieving robust CW lasing emission. [ 17,18 ] However, in previous reports, these single‐crystalline structures only served as free‐standing micro‐/nanolasers, which exhibited relatively weak optical confinement. Vertical cavity surface emitting lasers (VCSELs) by using high‐reflectance distributed Bragg reflectors (DBRs) is an effective configuration for providing a strong confined optical field to realize low‐threshold CW lasers.…”
Section: Figurementioning
confidence: 99%